Ciało ludzkie w dyskursie naukowym wieków dawnych. Konteksty = The human body in the scientific discourse of past centuries. Contexts - Rejter, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study, various contexts (cultural - civilizational, social, philosophical, etc.) concerning the issue of the human body, which were reflected in historical scientific discourse, are presented. Observations are limited to the field of medicine, whose discourse, by its very nature, focuses on somatic issues. The acceptance of the thesis that it is valid to consider various contexts of scientific discourse determines the success of research on this communicative and cultural phenomenon. This is particularly important when observing the transformations of discourse, its dynamics associated with the specific eras in which it functioned.
Keywords: dyskurs; dyskurs naukowy; dawny dyskurs naukowy; ciało; konteksty dyskursu; discourse; scientific discourse; historical scientific discourse; body; contexts of discourse